Zebrafish as animal model for aquaculture nutrition research - Ulloa, Pilar E.; Medrano, Juan F.; Feijoo, Carmen G. (Frontiers in Genetics, 2014)
The aquaculture industry continues to promote the diversification of ingredients used in aquafeed in order to achieve a more sustainable aquaculture production system. The evaluation of large numbers of diets in aquaculture species is costly and requires time-consuming trials in some species. In contrast, zebrafish (Danio rerio) can solve these drawbacks as an experimental model, and represents an ideal organism to carry out preliminary evaluation of diets. In addition, zebrafish has a sequenced genome allowing the efficient utilization of new technologies, such as RNA-sequencing and genotyping platforms to study the molecular mechanisms that underlie the organism’s response to nutrients. Also, biotechnological tools like transgenic lines with fluorescently labeled neutrophils that allow the evaluation of the immune response in vivo, are readily available in this species. Thus, zebrafish provides an attractive platform for testing many ingredients to select those with the highest potential of success in aquaculture. In this perspective aspects related to diet evaluation in which zebrafish can make important contributions to nutritional genomics and nutritional immunity are discussed.